2021
DOI: 10.3390/app11052339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citric Acid on Color Changes of Calcium Silicate-Based Cements an In Vitro Study

Abstract: The aim of the present in vitro study was to investigate the effects of 10% and 40% citric acid (CA) on the color of calcium silicate–based cements (CSCs) in comparison to the effects of common root canal irrigants. Samples of six CSCs (n = 6)—ProRootMTA (Dentsply, Tulsa, OK, USA, Biodentine (Septodont, Saint Maur des Fosses, France), MTA Plus (Avalon Biomed Inc, by Prevest Denpro Limited, Jammu, India), MTA Repair HP (Angelus, Londrina, PR, Brazil), Ortho MTA (BioMTA, Seoul, Korea), and Retro MTA (BioMTA, Seo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A total of 16 papers were included into the group discussing the physicochemical parameters of MTA HP [ 5 , 16 , 17 , 23 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The analysed selected physicochemical parameters of MTA HP, together with the most important results are given in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 16 papers were included into the group discussing the physicochemical parameters of MTA HP [ 5 , 16 , 17 , 23 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The analysed selected physicochemical parameters of MTA HP, together with the most important results are given in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
“…This feature is an undisputed advantage over the conventional MTA containing bismuth oxide as a radiopacifier [ 31 ]. Metlerska et al (2021) analyzed the effects of 10% and 40% citric acid (CA) on the color of calcium silicate-based cements (CSCs) in comparison to the effects of common root canal irrigants [ 35 ]. It was found that MTA repair HP was least sensitive to NaOCl solution of all the tested CSCs materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that residues of NaOCl could penetrate into dentin, and it was very difficult to remove from root canals. NaOCl changes the color of CSCs containing bismuth oxide [46]. When NaOCl came into contact with bismuth and other heavy metal oxides, a black precipitation appeared.…”
Section: Discussionmentioning
confidence: 99%